Rapid High‐Contrast Photoreversible Coloration of Surface‐Functionalized N‐Doped TiO2 Nanocrystals for Rewritable Light‐Printing. Issue 28 (19th May 2022) - Aleisa, Rashed; Feng, Ji; Ye, Zuyang; Yin, Yadong
Abstract: Pristine titanium dioxide (TiO2 ) changes color from white to black when it is reduced from Ti IV to Ti III by photoexcited electrons. However, the black coloration requires substantial light energy to create, and it vanishes instantaneously upon exposure to air. This work reports the synthesis of surface‐functionalized N‐doped TiO2 nanocrystals that rapidly change color (i.e., within seconds) from whitish to black under low‐power irradiation with excellent color stability in atmospheric conditions. The N‐doping plays a critical role in promoting the surface‐adsorption of polyol groups to stabilize the Ti III species and accelerate the coloration process. A rewritable paper fabricated using these nanocrystals exhibits excellent writing and erasing reversibility in response to UV irradiation and oxygen exposure. The low‐cost, rapid response, excellent reversibility, and good color stability are vital advantages of N‐doped TiO2 nanocrystals for color‐switching applications. Abstract : Surface‐functionalized N‐doped TiO2 nanocrystals are synthesized with controllable Ti III stability, displaying reversible color switching between whitish and black upon light illumination and controlled oxidation. They can be used as a rewritable material to produce high‐resolution printing and writing with excellent cyclability, promising for applications such as optical data recording, smart windows, and oxygen sensors.